Legacy [compact disc, unabridged] - Roberts, Nora (Macmillan Audio, 2021)
After launching her own line of yoga and workout videos, Adrian Rizzo begins receiving death threats, which lead her back home to Maryland, where she, with the help of her childhood crush, must find the truth when the threats escalate to murder.